Studies on the Proliferation of Copper Pheasant (Phasianus soemmerringii scintillans): I. Results by Artificial Insemination - MARU, NAOMARU; ICHINOE, KENJI; HIRABAYASHI, TADASHI; SAITO, NOZOMU (Japanese poultry science, 1968)
It was reported previously by authors that artificial insemination was succeeded in copper pheasants. In this paper, data were collected from successing experiments performed during 5 years period (1963-1967), using 62 birds (_??_14, _??_48), on their egg laying, fertility and hatchability, sex-ratio in chicks and their growth. The results obtained were as follows: 1. The mean number of eggs laying and the laying periods were 19.8 (5-40) eggs and 55. 7 (10-97) days respectively, and also considerable individual differences were observed among them. The peak production of eggs was considered to be from the middle of April to that of May, and also high fecundity was observed in 3 or 4 ages than the other age. 2. The fertility and the hatchability (to fertilized eggs) in copper pheasants by using artificial insemination were 84.3% and 84.0% respectively. 3. The semen was collected from the beginning of March to that of June, and also more volume of semen was collected from the middle of March to that of April. The mean volume of semen was 0.025 (0.005-0.1)ml, and 3 or 4 ages of birds were observed to be the adequate age to collect the semen. 4. From these results, authors concluded that the breeding ages in copper pheasants were considered to be 3 or 4 ages, and the synchronization of the breeding season between sexes might be necessary to get the better results, for in males the breeding season was one month earlier than that of females. 5. Generally speaking, female chicks were hatched more than males, and this tendency was clear in the case of mating of parents in the high fertilities. Some relation might be exsisted between the ranking of egg laying and the sex-ratio. 6. On the growth of chicks, the differences were observed between sexes from 4 weeks of age.